Sewage sludge management at the municipal wastewater treatment plant - Poproch, Dominika; Cimochowicz-Rybicka, Małgorzata; Górka, Justyna; Łuszczek, Bartosz (Instal, 2022)
The article presents the quantitative balance of sewage sludge and the energy balance at the municipal sewage treatment plant Kraków-Płaszów. As a result of the analyzes, it was shown that 85% of the sludge is subjected to thermal treatment, and the remaining part is transported outside the treatment plant. After burning the sludge, the ashes are managed by specialized external companies (mainly construction ones). The main direction of biogas management is its use for the production of heat and electricity. Thanks to the produced own energy, it is possible to cover 100% of the demand for heat and about 40% for electricity. For the Kraków-Płaszów WWTP, in 2021, the average value of the indicator specifying the amount of electricity consumed, per 1 m3 of treated sewage, was 0.34 kWh / m3.
Keywords: wastewater treatment plant; sewage sludge; biogas; energy balance